1984
DOI: 10.1159/000183240
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Hemodialysis: High Risk Patients for Arrhythmias?

Abstract: Patients with end-stage kidney disease untergoing chronic maintenance dialysis (HD) are a high risk group for sudden death due to cardiovascular complications. It was the aim of the study to investigate the quantity and quality of arrhythmias during HD and between two consecutive HD (interval, I) with regard to the reproducibility of the expected results. 15 patients (8 males, 7 females) underwent continuous Holier monitoring (LT-ECG) under ambulatory conditions over 96 h including two HD (HD 1 + HD2) and two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
1

Year Published

1987
1987
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(18 citation statements)
references
References 12 publications
2
15
1
Order By: Relevance
“…Previous evidence has suggested that the high incidence of ventricular arrhythmias detected in previous studies could be due to differences in patient recruitment and variables, including age, disease etiology, dialysis vintage and duration, and concomitant medication. [7] We found no such association between these variables and the frequency of PVCs or arrhythmias. Furthermore, the use of digoxin in patients on maintenance HD has been shown to increase the incidence of occult and potentially serious ventricular ectopy [23] and also potentially contribute to the high incidence of PVCs and CVAs in HD patients.…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…Previous evidence has suggested that the high incidence of ventricular arrhythmias detected in previous studies could be due to differences in patient recruitment and variables, including age, disease etiology, dialysis vintage and duration, and concomitant medication. [7] We found no such association between these variables and the frequency of PVCs or arrhythmias. Furthermore, the use of digoxin in patients on maintenance HD has been shown to increase the incidence of occult and potentially serious ventricular ectopy [23] and also potentially contribute to the high incidence of PVCs and CVAs in HD patients.…”
Section: Discussioncontrasting
confidence: 54%
“…[5] Consequently, there have been a number of studies looking at the potential pro-arrhythmogenic effects of HD, which reported the frequency of dialysis induced arrhythmias as anywhere in the range of 5-75% of treatments. [6,7] The presence of both potentially life-threatening complex ventricular arrhythmias (CVAs) and premature ventricular complexes (PVCs) has been associated with increased morbidity and mortality. CVAs (defined as Lown score of 3 and above) are reported in up to 35% of HD patients during treatment [8] and associated with negative prognostic factors including new coronary events [9] and silent myocardial ischemia.…”
Section: Introductionmentioning
confidence: 99%
“…In our opinion analysis of data support Rombol`a idea that some stressors such as fluid overload, increase in blood pressure and the changes in pH and bicarbonates, may act as trigger of ventricular arrhythmias [26]. Obviously this may be particularly true for patients with cardiomyopathy, left-ventricular hypertrophy, coronary artery disease and cardiac heart failure, which provide the perfect backdrop for arrhythmias to occur [27].…”
Section: Discussionsupporting
confidence: 51%
“…Finally, the drugs used by some of the patients receiving anti-arrhythmic therapy may also be dialyzable. Such patients may, for this reason, be susceptible to arrhythmia during or after hemodialysis (Kimura et al,1989;Weber et al, 1984). Prevalence of atrial fibrillation as one of the arrhythmia types was reported to be 27%, which is way above 0.5-1% seen in the general population (Genovesi et al,2008).…”
Section: Arrhythmiasmentioning
confidence: 99%